THE EFFECT OF DIET MODIFICATION ON THE DYNAMICS OF INSULIN RESISTANCE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Diet modification is one of the key non-drug methods for correcting insulin resistance in patients with type 2 diabetes. This article analyzes current clinical data, including randomized controlled trials, meta-analyses, and large cohort observations published between 2010 and 2025. Particular attention is paid to assessing the dynamics of insulin resistance indicators (HOMA-IR, fasting insulin level, euglycemic index) against the background of various dietary patterns, including the Mediterranean diet, low-carbohydrate schemes, low-glycemic index and low-load diets, intermittent fasting, and increased dietary fiber intake.